(3RHOI GdCUhds - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3CHgi CUd Ydjg GdNWGH hEdi bhd aVd jfJei Edjg s
(3BNQgG (B:s
(3CeG JHY efgG GdCbhi hGdRe eG gh CbQH Edi GdJbhi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(2/258) s
Keywords: (3abg GdePGgH GdCNQis